The outbreaks of termites (Coptotermes Curvigna Thus) on rubber trees (Hevea Brasiliensis) at Rubber Research Institute Malaysia (RRIM) Bukit Kuantan, Pahang. / Haryanti Abd Rahim - Abd Rahim, Haryanti (Faculty of Plantation and Agrotechnology, 2016)
Rubber (Hevea brasiliensis) was originally a native tree from Amazon and in early 20th century, it was introduced in Africa. The termite cause significant economic damage to rubber trees which is the species of Coptotermes curvignathus. The main objective of the study is to estimates the termite infestation that cause damage in rubber plantation, evaluated the related factor that affect the termite infestation such as rainfalls and to determine the best or suitable time to use termiticide to control termite infestation on rubber plantation. The site selection of study at (RRIM) Bukit Kuantan which located in Kuantan Pahang with the total hectare in this research station is 860.935ha. Method that has been used is collection of secondary data for termite infestation the data was recorded by staff for two years and amounts of rainfall for 2014 and 2015 from Malaysian Meteorology Department. The comparison between two years shows that amounts of termites infestation at 2014 is higher than 2015, this is due to the factor amounts of the rainfalls. During the year of 2014 and 2015 the monthly rainfalls amount which are 3086.2 mm and 1605.1 mm for annual. So, there is There are also no significant difference show by ANOVA between termites infestation with the amounts of rainfalls at 2014 and 2015(P>0.05) which are 0.176 and 0.192. During time of draught or dry period termite infestation at the highest number and during wet season they are decrease number of termite infestation .For the best time or suitable time to use temicide to control termite infestation on rubber plantations is during dry period because the activity of termite at maximum. So there is chance to kill termite queen and will save more money if using at the right time.